2022
DOI: 10.3390/microorganisms10010112
|View full text |Cite
|
Sign up to set email alerts
|

Cases of Acute Flaccid Paralysis Associated with Coxsackievirus A2: Findings of a 20-Year Surveillance in the Russian Federation

Abstract: Surveillance for acute flaccid paralysis syndrome (AFP) in children under 15 is the backbone of the Global Polio Eradication Initiative. Laboratory examination of stool samples from AFP cases allows the detection of, along with polioviruses, a variety of non-polio enteroviruses (NPEV). The etiological significance of these viruses in the occurrence of AFP cases has been definitively established only for enteroviruses A71 and D68. Enterovirus Coxsackie A2 (CVA2) is most often associated with vesicular pharyngit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
4
0
2
Order By: Relevance
“…Alternative explanations could include variation of pathogenic properties between subtypes that were circulating in different countries and at different times, or extensive circulation of these types among age groups that were less likely to have AFP because of unrelated causes. CVA2, which has been implicated in AFP cases in Russia and in Brazil [ 30 , 36 ], has been twice more common among AFP patients than average in the dataset; however, this was not statistically significant due to a small overall number of CVA2 isolations. On the other hand, three out of five CVA2—positive AFP patients had fever at the onset and residual paralysis, comparable with virus-induced poliomyelitis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Alternative explanations could include variation of pathogenic properties between subtypes that were circulating in different countries and at different times, or extensive circulation of these types among age groups that were less likely to have AFP because of unrelated causes. CVA2, which has been implicated in AFP cases in Russia and in Brazil [ 30 , 36 ], has been twice more common among AFP patients than average in the dataset; however, this was not statistically significant due to a small overall number of CVA2 isolations. On the other hand, three out of five CVA2—positive AFP patients had fever at the onset and residual paralysis, comparable with virus-induced poliomyelitis.…”
Section: Discussionmentioning
confidence: 94%
“…Among 18 myelitis patients with residual paralysis ( Table 2 ), distribution of cytopathogenic agents was as follows: CVB1-6 and HAdVs (4 cases or 22.2% each), CVA2 (3 cases, 16.7%), EV-A71 (2 cases, 11.1%), and CVA16, E3, E6, E21, and E25 (1 case or 5.6% each). Previously, we had described cases of the disease with a clinical picture of poliomyelitis, for which the etiological role of CVA2 was suggested [ 30 ]. There were several more noteworthy cases among myelitis patients.…”
Section: Resultsmentioning
confidence: 99%
“…2 During the study period, residual paralysis (26.32%), muscle weakness (17.11%), 10.53% not followed, and 25% of the files with missing information over the study period were observed. 13,29 The most important difference between polio and other causes of AFP is the course; paralytic sequelae are common in polio, whereas other symptoms tend to heal in 60 days.…”
Section: Resultsmentioning
confidence: 99%
“…В литературе описаны единичные случаи выделения вируса из ЦСЖ: дважды был обнаружен EV-D68 [2,3], у одного пациента -CVА16 [3], еще у одного -CVA2 [4]. В 2016 г. на мышиной модели показана возможность EV-D68 вызывать парезы и параличи при периферическом (при внутримышечном -100 %, при интраназальном -2,7 %) введении [5]. У мышей, инфицированных EV-D68, отмечалось поражение мотонейронов передних рогов спинного мозга, топически соответствующих парализованным конечностям (как и у детей с ОВМ).…”
Section: Introductionunclassified
“…У мышей, инфицированных EV-D68, отмечалось поражение мотонейронов передних рогов спинного мозга, топически соответствующих парализованным конечностям (как и у детей с ОВМ). Также вирус, выделенный из спинного мозга инфицированных мышей, вызывал заболевание при инъекции наивным особям [5]. Это подтверждает биологическую достоверность связи между инфекцией EV-D68 и возникновением ОВМ.…”
Section: Introductionunclassified